1988
DOI: 10.1017/s0007485300013195
|View full text |Cite
|
Sign up to set email alerts
|

Habitat associations and seasonal abundance of coprophilous coleoptera (Staphylinidae, Hydrophilidae and Histeridae) in the Hluhluwe region of South Africa

Abstract: A total of 134 species of Coleoptera (100 of staphylinids, 13 of hydrophilids and 21 of histerids) was extracted from pads of cattle dung placed in four contrasting habitats in both Hluhluwe Game Reserve, Natal, South Africa, and the surrounding pastoral regions. Pads were exposed to colonists for 24 h on eight occasions over one year. Forty-six species and species complexes were captured in numbers sufficient to permit analysis of their distribution patterns. Of 27 species significantly influenced by vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Our results in four contrasting vegetation types associated to oak forests showed an amassing responses between beetle assemblages among vegetation types that might be related to particular preferences of each group as well as to inherent effects of seasonally and vegetation type conditions. First, an examination of the diversity for coprophile beetle families revealed that Staphylinidae and Scarabaeideae showed no strong differences for vegetation type preferences (although see below; Davis et al 1988;Dunn and Danoff-Burg 2007;Caballero et al 2009;Hopp et al 2010). Staphylinidae are generalist predators (Hanski 1987), and most dung beetles-Scarabaeideae-are considered opportunistic-they tend to use a large variety of dung types (Hanski and Cambefort 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Our results in four contrasting vegetation types associated to oak forests showed an amassing responses between beetle assemblages among vegetation types that might be related to particular preferences of each group as well as to inherent effects of seasonally and vegetation type conditions. First, an examination of the diversity for coprophile beetle families revealed that Staphylinidae and Scarabaeideae showed no strong differences for vegetation type preferences (although see below; Davis et al 1988;Dunn and Danoff-Burg 2007;Caballero et al 2009;Hopp et al 2010). Staphylinidae are generalist predators (Hanski 1987), and most dung beetles-Scarabaeideae-are considered opportunistic-they tend to use a large variety of dung types (Hanski and Cambefort 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Hanski and Koskela 1977, Baz 1988. Davis et al 1988, Doube andMacqueen 1991). Vegetation cover determines both abundance and species richness of this group of beetles.…”
mentioning
confidence: 99%
“…The beetles O. caff'er and Onitis viridulus Boheman were relatively scarce in the Hluhluwe trap catches (baited for 24 h), but these species preferentially colonise older dung (3-7 days old) (Doube et al, 1988) and are much more abundant in Hluhluwe than is suggested by the data in table 1. In contrast, there are other r-selected species which have not been successful in Australia.…”
Section: Discussionmentioning
confidence: 82%
“…Climate-matching followed by habitat-matching has permitted the selection and successful introduction of species, provided that they can be reared readily in the laboratory (Doube et al, in press). The same principles are likely to yield beneficial results when applied to the selection and introduction to Australia of predators and parasitoids of dung-breeding pest flies because they also show strong habitat affinities (Davis et aL, 1988). For example, species which are common in the Hluhluwe pastoral regions and which parasitise or prey upon dung breeding Haematobia (Doube & Huxham, 1987) are prime candidates for introduction to subtropical northern Australia.…”
Section: Discussionmentioning
confidence: 99%